The Role of Glucosamine Chondrotin Sulfate in the Treatment of Osteoarthritis of Knee - AlMukhtar, Sadeq A.; Al-Muktar, Sinan (AL-Kindy College Medical Journal, 2013)
Background: Osteoarthritis (OA) currently seems inevitable and unavoidable for a large swath of the population .its etiology relates to a strong ,but complex ,non mendelian genetic basis ,combined with mechanical and metabolic factors that cause molecular alterations the end results of which affect the whole joint .Glucosamine and chondrotin sulfate alone or in combination may be of benefit to a subgroup of individuals who have knee pain due to OA. Glucosamine has been shown to alter cartiage turn over in patients with OA undergoing physical training Aim of the study: To find the validity of glucosamine chondrotin sulfate in treatment of grade 1 and 2 OA. Methods: the sample of 280 patients (418 knee) were divided in to two groups , group A (132 patient) treated by classical methods by glucosamine chondrotin sulfate for one year. For both groups different parameters were used including pain stiffness effusion crepitus and genu varum and different radiological findings and we used MRI for evaluation pre and post treatment Result: Female/ male ratio was 2.89 the highest age group was ( 60-69) year regarding the clinical presentation of patients the commonest clinical presentation were pain and stiffness and the MRI finding including bone marrow edema shows good indicator for response to treatment . Conclusion: Pain ,stiffness and crepitus were common presentation of OARelief of pain andstiffness were related to decrease of effusion and bone marrow edema which is the result of using nonsteroidal anti-inflammatory drugs with glucosamine chondroitin sulfate more than when non steroidal anti- inflammatory drugs alone.